Palladium catalyzed domino reaction of 1, 4-disubstituted 1, 2, 3-triazoles via double C–H functionalization: one-pot synthesis of triazolo[1, 5-f]phenanthridines. Issue 49 (3rd May 2016) - Kumar, Avnish; Shinde, Sundar S.; Tiwari, Dharmendra Kumar; Sridhar, Balasubramanian; Likhar, Pravin R.
Abstract : A palladium catalyzed domino reaction of 1, 4-disubstituted triazoles involving homo- and heterocondensation is presented. The approach provides a simple, straight forward and a facile route to access triazolo[1, 5- f ]phenanthridines in high yields. Abstract : A palladium catalyzed domino coupling reaction of 1, 4-disubstituted triazoles via homocondensation with a second molecule is presented. The domino couplings involve the formation of biaryl and bi(hetero)aryl bonds through a five membered carbopalladacycle intermediate. The approach provides a simple, straight forward and facile route to access triazolo[1, 5- f ]phenanthridines in high yields. Furthermore, the developed protocol was extended to heterocondensation in the presence of norbornene.